Comparison study of lightly doped drain (LDD) and double diffused drain (DDD) to overcome hot carrier effect on 0.3um NMOS - Muhammad, Mohd Khairi (2009)
The aim of this project is to present the analysis and simulation of the comparison of Light Doped Drain (LDD) and Double Diffuse Drain (DDD) to overcome Hot Carrier Effect on 0.3um NMOS device. The project started with designing the NMOS device using the SILVACO TCAD simulation software.